Det religiøse nulpunkt - Sørensen, Jørgen Podemann (Religionsvidenskabeligt Tidsskrift, 2001)
Taking its point of departure in Frits Staal’s theory of ritual as a pure, meaningless activity, this paper identifies and further develops a somewhat similar, but more sophisticated Andamanese theory of ritual as an activity formally situated in point zero and, with a classical Daoist expression, “dealing with things in their state of not yet being.” This theory unites the formal aspects of existing theories of myth and ritual and rites of passage and permits an analytically important distinction between the situating and productive elements of ritual.